Measurement of CO2 in Water from an Ultraviolet Oxidizer for a Space-Worthy Wastewater Recovery System Using Raman Spectroscopy. Issue 1 (January 2023) - Farquharson, Stuart; Brouillette, Carl; Shende, Chetan; Farquharson, Duncan; Morrison, Chad
NASA has been developing and testing a water recovery system for over two decades to minimize the amount of water required for long duration human space missions. A key system component is the total organic carbon analyzer (TOCA) that determines if the recovered water is below the toxicology-defined health limit of 5 mg/L TOC and is safe to drink. The TOCA is composed of a liquid phase loop and a gas phase loop. The TOCA employs an oxidizer to convert the organics in the liquid phase to carbon dioxide (CO2 ) and a liquid–gas separator to isolate the CO2 for measurement in the gas phase by infrared spectroscopy. In an effort to reduce the consumables, mass, volume, and power of the system, we investigated the ability of surface-enhanced Raman spectroscopy (SERS), and Raman spectroscopy to measure 5 mg/L carbon in water. The SERS measurement employed silver colloids to increase sensitivity, while the Raman measurements used multiple mirrors to increase sensitivity. Here, we present SERS measurements of carbonate (CO3 =) at 3 mg/L carbon and Raman measurements of CO2 at 9 mg/L carbon in the effluent water of a new oxidizer being developed for a future TOCA. Both SERS and Raman techniques can determine TOC in the liquid phase, eliminating the need for the gas phase loop and associated supplies and replacement components, which could effectively decrease the size and weight of the current TOCA by as much as 50%. Graphical Abstract